ZBTB7A regulates CD95-mediated cell growth in colorectal cancer cell lines - Yanhong Bie; Meiying Bie; Wang Liu; Shufang Tao; Hongyu Xing; Linlin Kuang; Yi Song (PLoS ONE, 2025)
Zinc Finger and BTB Domain-containing7A (ZBTB7A) is a member of the transcription factor family that regulates the expression of numerous genes involved in cell proliferation and differentiation. Ubiquitously expressed in colon, stomach, and other tissues, ZBTB7A performs diverse functions including hematopoiesis, metabolism, and oncogenesis. Here we showed that ZBTB7A knockout inhibited the growth of colon cancer cells and reduced CD95 protein expression by decreasing CD95 mRNA transcription. Overexpression of ZBTB7A could partially restore both CD95 expression and CD95-mediated downstream Caspase2 and JNK2 expression. Furthermore, treatment with ZBTB7A specific inhibitor Curcumin effectively induced colorectal cancer cell death while reducing CD95 expression. These data indicate that ZBTB7A promotes colon cancer cell growth and survival, suggesting its potential as a therapeutic target for colorectal cancer.